Implementasi Network Attached Storage (NAS) Menggunakan Freenas Pada STMIK Lombok - Lalu Supriadi Kalaena; Wire Bagye (Jurnal Manajemen Informatika dan Sistem Informasi, 2018)
STMIK Lombok is an institution engaged in education that process data, about students, student practical data, lecturer data, and correspondence. Media file storage applied STMIK Lombok still on a separate computer, both academic data and practical data, so to access the file must be done on the computer where the storage. Based on the capability of Network Attached Storage in local network, by looking at the need of data storage media on the network at STMIK Lombok and the observation result then designed a network architecture by utilizing Network Attached Storage device with focus on fast storage and data transfer process. Stages of research include Data collection, design, and methods of testing To be able to help solve the problem of separate data access then implemented Network Attached Storage (NAS) which is a network to perform distribution of storage assets owned by the server of a network system that has the advantage of faster access to data stored through Local Area Network, minimal cost and cheap and easy maintenance, from setup to configuration, and available Open Source Software. After doing the testing phase it can be concluded that FreeNas as an operating system used for the processing of network storage media is very capable of handling the task well and the facilities that exist in it is very supportive in storage and accessing files. FreeNas web is very helpful and allows users to configure it other than it can be used without having to spend a large cost, and with the facilities in the FreeNas.